Expression of molecular clones of v-myb in avian and mammalian cells independently of transformation. - Lipsick, J S (1986)
We demonstrated that molecular clones of the v-myb oncogene of avian myeloblastosis virus (AMV) can direct the synthesis of p48v-myb both in avian and mammalian cells which are not targets for transformation by AMV. To accomplish this, we constructed dominantly selectable avian leukosis virus derivatives which efficiently coexpress the protein products of the Tn5 neo gene and the v-myb oncogene. The use of chemically transformed QT6 quail cells for proviral DNA transfection or retroviral infection, followed by G418 selection, allowed the generation of cell lines which continuously produce both undeleted infectious neo-myb viral stocks and p48v-myb. The presence of a simian virus 40 origin of replication in the proviral plasmids also permitted high-level transient expression of p48v-myb in simian COS cells without intervening cycles of potentially mutagenic retroviral replication. These experiments establish that the previously reported DNA sequence of v-myb does in fact encode p48v-myb, the transforming protein of AMV.